Poverty Alleviation Strategy Through the Sharia Economic Model - Kheqal Fitradinata; Muhammad Fadhli; Riyandi Fatur Nugraha; Zulfikar Hasan (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
Poverty is one of the biggest challenges in developing countries like Indonesia. Although various efforts have been made, the results of poverty reduction have not been sufficient, so a more comprehensive and sustainable approach is needed. The application of the sharia economic model, based on Islamic principles such as justice, balance and sustainability, offers a holistic and fair solution to overcoming poverty. Sharia economics emphasizes the equal distribution of wealth through zakat, alms, infaq and waqf mechanisms which are significant in redistributing wealth and empowering the community's economy. The research method used is qualitative by reviewing documents and related literature. Data analysis was carried out interactively to understand primary and secondary data sources. From the results of the analysis, it appears that the implementation of sharia economic principles has made a positive contribution in reducing poverty rates in Indonesia, although challenges in poverty alleviation still remain. Therefore, commitment and cooperation between the government, the private sector and the wider community is needed to continue to develop and implement strategies that are more effective in overcoming the problem of poverty as a whole. The conclusion of this study is that the application of the sharia economic model has great potential in alleviating poverty in Indonesia.